Online Medical Teaching in COVID-19 Era: Experience and Perception of Undergraduate Students - HAMEED, Tariq (Maedica (Bucur), 2020)
Introduction: Rapid emergence of COVID-19 as pandemic has affected the life of almost every human being and has changed the way people used to interact. It has also affected medical education and clinical training, and forced medical schools to switch over to online mode of teaching. The aim of this study was to learn about the experience and perception of undergraduate students regarding online teaching. Methods: This is a cross sectional observational study conducted among the undergraduate students of Hamdard Institute of Medical Sciences and Research, New Delhi, India. A validated electronic questionnaire with nine questions was sent to 177 students as Google FormsTM. Responses from 161 students were received and analyzed using SPSS software. Results:The majority of students were satisfied with the frequency, organization, content and preparedness of classes. Half of students were neither satisfied with the amount of syllabus covered nor online teaching method. Among various teaching methods, live online lectures were most common and they were also preferred by the majority of students. Most students want hybrid or blended teaching in the post COVID-19 era. Conclusion: Online or e-teaching alone is not preferred by the majority of students. Lack of interpersonal interaction is the most likely reason for this. Hybrid or blended teaching holds the future of medical education as it is more student friendly and efficient.